7+3(2х+1)=4
7+6х+3=4
10+6х=4
6х=4-10
6х=-6
х=-1
хорошего дня!
7 + 3( 2х + 1) = 4
7 + 6х + 3 = 4
6х = 4 - 3 - 7
6х = -6
х = -1
ответ: -1
Объяснение: перемножаем числа на содержимое скобки и нужно соблюдать знаки, и при перенесении на другую сторуну чисел.
7+3(2х+1)=4
7+6х+3=4
10+6х=4
6х=4-10
6х=-6
х=-1
хорошего дня!
7 + 3( 2х + 1) = 4
7 + 6х + 3 = 4
6х = 4 - 3 - 7
6х = -6
х = -1
ответ: -1
Объяснение: перемножаем числа на содержимое скобки и нужно соблюдать знаки, и при перенесении на другую сторуну чисел.